Ekspektasi Mengenai Garis Lurus - Aulia Ibrahim Yeru (JURNAL RUPA, 2016)
The author's work in this project takes inspiration from many production processes that occur in space consumption. This author’s work is focused its idea on the question whether the form that become cornerstone for designing cities or spaces has impact that could be felt directly by its inhabitants. The context for this work is Southern Square (Alun-Alun Kidul), Yogyakarta. For author himself, Yogyakarta become appaling because its design, as a whole, based on the symettrical line which extends from Merapi Mountain to Indian Ocean. This is marked by the presence of Merapi Monument, located at the intersection of Jalan Sudirman and Jalan Margo Utomo. That symmetry axis symbolizes the philosophy or belief system of the Sultanate of Yogyakarta. The question that author try to raise is whether this symmetrical has direct impact physically and psychologically? Borrowing the traditional game called masangin that practiced everyday in Southern Square as artmaking method, author intend to test the presence of symmetrical both physically and psychologically in several places, those are Southern Square, Gasibu Bandung, and in footpath around Institut Teknologi Bandung buidings. With eyes blindfolded, author tried to make straight line thorugh those axis of symmetries.